PENERAPAN RADIOTERAPI PADA PENGOBATAN KANKER PAYUDARA - Nurhayati Nurhayati; Neng Nenden Mulyaningsih (Schrodinger Jurnal Ilmiah Mahasiswa Pendidikan Fisika, 2020)
Breast cancer is the most common cancer in women, which is about 25% of all cancer incidents and is the second leading cause of death after lung cancer. Breast cancer can also occur in men, with a ratio of 1: 100 when compared to women. Cancer is a disease that causes high mortality in the world. Based on WHO data, in 2015 there were 8.8 million deaths caused by cancer.  Various methods have been developed to treat cancer, one of which is by using radiation therapy or radiotherapy. According to the International Agency for Research on Cancer (IARC), of the 10.9 million people diagnosed with cancer worldwide each year, about 50% need radiotherapy. The use of radiation for cancer therapy has not been widely used and is still limited in Indonesia. The purpose of writing this article is to describe the use of radiotherapy in the treatment of breast cancer through literature searches. The results of the literature search show that radiation technology has existed in Indonesia since 1927. Radiotherapy has become one of the important therapies in cancer treatment in Indonesia. The increasing number and development of radiotherapy facilities are expected to reduce the prevalence of cancer in Indonesia.